SCHOOL INCLUSION OF ATYPICAL CHILDREN IN BASIC EDUCATION FROM THE PERCEPTIONS AND EXPERIENCES OF MOTHERS (International Seven Journal of Multidisciplinary, 2026)
The Law of Guidelines and Bases recognizes Special Education as a form of school education offered free of charge, complementing the learning process, and being offered primarily in the regular school system, favoring integration into the social context; seeking to end social exclusion, banning these people from any social activity, considering them disabled, incapable of working and useless to society. Our objective in this study was to understand the maternal view on the schooling trajectory of an atypical child in the regular school system. Eleven mothers of atypical children participated, and the inclusion criteria were that their children were of school age and agreed to participate voluntarily. The exclusion criteria were mothers of children who were not of school age at the time of the interview. For data collection, we used semi-structured interviews and a questionnaire with key words of interest to the study, divided into Axis 1, composed of questions related to the child's schooling; and Axis 2, composed of questions related to inclusion. The study was a diagnostic sample that points to the need for public inclusion policies to be more elaborate and comprehensive, considering leisure activities and socialization outside of school. The results obtained show us how challenging it is to deal with atypical children from the very first signs, as it is a small sample of the complexity involved in an atypical child; we suggest studies to reflect on the challenges both in obtaining the diagnosis and those encountered in the schooling of atypical children.